2016
DOI: 10.1016/j.scienta.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

A review of optimal systems for organic production of blueberry and blackberry for fresh and processed markets in the northwestern United States

Abstract: Various production systems have been evaluated in blackberry (Rubus L. subgenus Rubus Watson) and northern highbush blueberry (Vaccinium corymbosum L.) in certified organic research trials for 5 and 8 years, respectively, in Aurora, OR, USA (lat. 45°16'47"N, long. 122°45'23"W) and are reviewed here. Treatments included cultivar, weed management, and fertilizer source in both crops; planting system, use of municipal yard debris compost, and fertilizer rate in blueberry; and effectiveness of liquid sources of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…It is possible that the cultivars differed in their adaptability to the various fertility regimes caused by the amendmentmulch treatments and fertilizers used in our study. Larco et al (2013aLarco et al ( , 2013b and Strik (2016) observed differences in plant growth and yield between 'Duke' and 'Liberty' when fertilized with fish emulsion or feather meal in a certified organic production system. Incorporation of a preplant amendment, particularly douglas fir sawdust in our region, is common (Julian et al, 2011a(Julian et al, , 2011b and has been shown to improve growth and production over the long-term compared with no preplant amendment in conventionally managed blueberry fields (Nemeth et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It is possible that the cultivars differed in their adaptability to the various fertility regimes caused by the amendmentmulch treatments and fertilizers used in our study. Larco et al (2013aLarco et al ( , 2013b and Strik (2016) observed differences in plant growth and yield between 'Duke' and 'Liberty' when fertilized with fish emulsion or feather meal in a certified organic production system. Incorporation of a preplant amendment, particularly douglas fir sawdust in our region, is common (Julian et al, 2011a(Julian et al, , 2011b and has been shown to improve growth and production over the long-term compared with no preplant amendment in conventionally managed blueberry fields (Nemeth et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Larco et al (2013a) found lower soil pH under weed mat mulch than under a yard-debris compost + sawdust mulch in organic blueberry. However, use of a yard-debris compost only as part of a mulching program had benefits for mitigating the decline in soil pH that occurs with fertilization over time, while maintaining soil pH within the desired range for blueberry (Larco et al, 2013a;Strik, 2016). Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The northwestern United States is the largest growing region for blueberries (Vaccinium corymbosum L.) in the country and, in 2018, accounted for 48% of the total production (North American Blueberry Council, unpublished data). This region also accounts for more than 60% of the total U.S. organic production of blueberries, which continues to increase due to strong markets and an ideal climate for high yield and quality (DeVetter et al, 2015;Fernandez-Salvador et al, 2017;Strik, 2014Strik, , 2016. However, 15 years ago, organic production only accounted for 2% of the total blueberry area in the region (Strik, 2016).…”
mentioning
confidence: 99%